Towards an expanded role for Asian currencies: Issues and prospects - Hwee Kwan Chow (Asian Development Bank Institute (ADBI), 2011)
Notwithstanding incumbency advantages and network effects enjoyed by the United States (US) dollar, considerations about the stability of its value have led Asian countries to fear they are holding their foreign exchange reserves in a depreciating currency. At the same time, it pays for the regional countries to adjust their reserve currency composition to match the point of reference of their exchange rate policy. This paper examines empirically which regional currency or currencies seem to matter for exchange rate determination in Asia beyond the very short term. To this end, we employ country-specific Vector Autoregressive (VAR) models to compare the relative impact which fluctuations in the Asian Currency Unit (ACU), yuan, and yen separately have on movements of Asian currencies. Contrary to recent evidence based on daily data, we found monthly exchange rates variations in the region are more heavily influenced by the cumulative effect of key Asian currencies than by the yuan or the yen individually within the sample period we used. To the extent that exchange rates in the region shift over time from benchmarking the US dollar towards a broad range of Asian currencies, Asian central banks will find it more attractive to cross-hold Asian bonds. This calls for the development of deep private markets in such assets, as well as institutional prerequisites for internationalizing key regional currencies.
Keywords: F31; F33; 330; Währungskorb; Renminbi; Yen; Wechselkurs; Kapitalmarktliberalisierung; Reservewährung; Wechselkurspolitik; Asien